Phase dependent magnetic properties of Ni-Au alloy nanowires - Prasad, R. V. S.; An, Boo Hyun; Shin, Youngmin; Jeon, In Tak; Suh, Jin-Yoo; Kim, Young Keun; Choi, In-Suk (ELSEVIER, 2014)
Binary alloy nanowires of mutually immiscible Ni-Au system are synthesized by electrodeposition method. Here, we incorporate the concept of alloy design into nanowires to effectively engineer and control the magnetic properties of nanowires. Saturation magnetization and coercivity values of as-deposited Ni-Au alloy nanowires strongly correlate with either the phases present or to the dissolution of gold to nickel. The magnetic properties, however, were significantly affected upon annealing, which is correlated with the structural evolution of a weakly magnetic metastable hcp-Ni phase. We report here the detailed investigation on phase transformations in Ni-Au alloy nanowires and their effect on magnetic properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: CO